On quasi-Lamb modes in the system "elastic half-space — layer of an ideal compressible fluid" - Bahno, O.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
The propagation of quasi-Lamb waves in the system "layer of ideal compressible fluid — elastic half-space" is studied, by using the three-dimensional equations of the classical elasticity theory for a solid body and the lineari zed Euler equations for a fluid. The dispersion curves for normal waves over a wide range of frequencies are constructed. The influence of the thickness of a layer of the ideal compressible fluid on the phase velocity dispersion of the quasi-Lamb modes in a hydroelastic waveguide is analyzed. A criterion for the existence of the quasi-Lamb waves in hydroelastic waveguides is proposed. The numerical results obtained are presented in the form of plots and analyzed.